Simulating the impact of ground surface morphology on archaeological orientation patterning. (February 2021) - Li, Li; Lin, Sam C.; Peng, Fei; Patania, Ilaria; Guo, Jialong; Wang, Huimin; Gao, Xing
Abstract: The orientation of artifacts and faunal remains within archaeological deposits are useful for understanding past processes that led to the formation of these deposits. This is because post-depositional processes move clasts in particular ways, causing non-random patterning in clast orientation arrangements. On the other hand, when assemblages exhibit a randomly distributed bearing orientation and minimal tilt, it is commonly assumed that the remains are of a primary depositional context with limited influence from taphonomic mechanisms. Yet, this null expectation about in situ artifact orientation is seldom demonstrated empirically. In this study, we develop a GIS simulation approach to model artifact discard on real-world surfaces of distinct terrain and slope morphologies. Our findings demonstrate that an uneven ground surface relief can cause in situ discards to have a more variable plunge orientation arrangement. Using the Upper Paleolithic site of Shuidonggou Locality 2 as a case study, we show that the horizontally distributed artifact 'layers' at the site exhibit orientation profiles that are consistent with the simulated outcome. This finding suggests the possibility of using archaeological orientation patterning as a proxy for past ground surface relief and morphologies. Highlights: Simulated artifact discard on models of real-world open land surfaces. Ground surface relief has notable influence on the orientation of in situ artifacts. Assemblage orientation can vary contextually without taphonomic influences. Artifact orientation at Shuidonggou Locality 2 explainable by surface relief variation.